Rozumienie hipotezy w słownikach i podręcznikach zakresu nauk społecznych = Understanding hypothesis in dictionaries and textbooks in the field of social sciences - Narkiewicz-Niedbalec, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author analyses selected examples of definitions of hypotheses. They come from dictionaries, encyclopaedias and social science textbooks. The author shows diversity of the adopted definitions and the consequences of their application. She refers to the examples of logic, psychology, and sociology. The author also recalls the position of representatives of quantitative and qualitative research. She is in favour of an explicit choice of one definition of a hypothesis and of its consistent application it in editing hypotheses in empirical research.
Keywords: hipoteza; hipoteza w badaniach ilościowych i jakościowych; warunki stawiane hipotezom; hypothesis; hypothesis in quantitative and qualitative researches; conditions posed upon hypotheses